Idiopathic retinal vasculitis, aneurysms, and neuroretinitis (IRVAN) syndrome: clinical perspectives - Bajgai P (Dove Medical Press, 2017)
Priya Bajgai, Deeksha Katoch, Mangat Ram Dogra, Ramandeep Singh Advanced Eye Center, Postgraduate Institute of Medical Education and Research, Chandigarh, India Abstract: Idiopathic retinal vasculitis, aneurysms, and neuroretinitis (IRVAN) syndrome typically affects young, healthy individuals. Despite the dramatic fundus appearance seen in this syndrome, these patients are usually asymptomatic. The syndrome includes peculiar vascular abnormalities in the form of multiple aneurysmal dilatations seen along retinal arterioles and optic nerve-head arterioles, which are best appreciated on fluorescein angiography. Neuroretinitis and retinal vasculitis are seen in all patients, and manifested by staining of the optic nerve head and diffuse leakage from vessels, mainly arterioles, on fluorescein angiography. The devastating vision-threatening outcomes of this syndrome include exudative retinopathy and extensive peripheral retinal nonperfusion areas, which can eventually lead to neovascularization. This review summarizes current knowledge on the variable clinical aspects of this disease, highlighting diagnostic and treatment strategies. Keywords: IRVAN, aneurysmal dilatation, neuroretinitis, panretinal photocoagulation